Mimesis and Revolution - Villalobos-Ruminott, Sergio (Re-presentaciones: Periodismo, comunicación y sociedad, 2023)
From the theatrical representation of the modern revolution, we try to question the economimesis that supplies the various representations of revolutionary and insurrectional processes. More than sustaining a substantive difference between the two, we show how a hermeneutic operation is always exerted to justify their difference in nature and value. This differentiation is based on a certain onto-mimetology, that is, on certain understanding of historicity anchored to the determinants of the modern sovereign theater, which is articulated by the figures of the national State, the community, the question of belonging, and the common destiny of the people. Said sovereign theater works according to a specular-spectacular model that betrays the co-belonging of state and popular sovereignty, which in turn defines the framework (or scenario) of western aesthetic and political modernity.